Perubahan Sosial Fenomena Media Sosial Digitalisasi terhadap Minat Belajar Siswa Sekolah di Depok - Nurkaidah, Nurkaidah; Bahri, Saiful (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Advances in information technology have had a significant impact on students in the learning process, especially through the use of social media which is an important part of the current digital era. The younger generation, especially those who are still pursuing formal education, feel very helped by this development. One very beneficial aspect of the digital era is the ability to use search engines to quickly and efficiently obtain the latest information, knowledge and news related to the world of education. The use of internet technology and social media has also penetrated the teaching and learning process in schools. Intensive use of social media influences student development, which can have positive or negative effects, depending on the individual's awareness in using it. It is important for students to use social media wisely, perhaps with parental supervision, as not all content available on social media is useful or accurate. This research is based on a literature study and methodology that involves collecting sources from currently relevant scientific journals. This approach involves analyzing various previous studies regarding the influence of social media phenomena on students' interest in learning. This phenomenon shows that social media can provide a positive boost to students' interest in learning by making access to information easier. However, the influence of social media can also have negative impacts, such as addiction, exposure to pornographic content, and access to information that is not filtered wisely among students.